Light flash and odor during proton beam therapy for pediatric patients: a prospective observational study - Mizumoto, Masashi; Oshiro, Yoshiko; Miyamoto, Toshio; Sumiya, Taisuke; Baba, Keiichiro; Murakami, Motohiro; Shimizu, Shosei; Iizumi, Takashi; Saito, Takashi; Makishima, Hirokazu; Numajiri, Haruko; Nakai, Kei; et al. (Frontiers in Oncology, 2022)
Light flash and odor during radiation therapy are well-known phenomena, but the details are poorly understood, particularly in pediatric patients. Therefore, we conducted a prospective observational study of these events in pediatric patients (age <20 years old) who received radiotherapy at our center from January 2019 to November 2021. Light flash and odor were evaluated using a patient-reported checklist including the presence, strength, and duration of the phenomenon, and color of light or type of odor. 53 patients who received proton therapy (n=47) and photon radiotherapy (n=6) were enrolled in this study. The median age of the patients was 10, ranged from 5 to 20. The patients who was able to see the light flash was 4, and all of them received retina irradiation. This was equivalent to 57% of the patients who received radiotherapy to retina (n=7). The light was bright and colored mainly blue and purple, which seemed to be consistent with Cherenkov light. Odor was sensed by 9 (17%) patients, and seven patients of the 9 received nasal cavity irradiation. This was equivalent to 41% of the patients who received nasal cavity irradiation (n=17). Other 2 patients received proton therapy to brain tumor. The odors were mainly described as plastic, burnt and disinfectant, which may be caused by ozone generated during irradiation. These data suggest that pediatric patients with retinal and nasal cavity irradiation frequently sense light flashes or odor. So adequate care is necessary so that these patients are not worried about this phenomenon.